PELATIHAN BAHASA INGGRIS DASAR PADA MAHASISWA BARU DYNASTY COMPUTER TAHUN AJARAN 2022/2023 - Fadli, Noval (Ensiklopedia of Journal, 2024)
Basic English Learning Training is one of the community service programs that aims to provide English learning. This activity was carried out English lecturers. The activities carried out during the training were the presentation of basic English material so that students more understand learning English. In Community Service, Basic English Training is given to Dynasty Computer students who most need capacity building. A total of 11 meetings, apart from pretest and posttest, were held. As a result, the Basic English proficiency of Dynasty Computer students has increased. However, persistence is still needed from students to want to study better so that their skills increase significantly. Several conclusions were drawn that the PPM program received good reception from Dynasty Computer's new students in general. This can be seen from the students' interest in the training program; This program provides motivation to students to improve their English skills after they understand better that English is important for their future.Keyword : Training, Basic English